Pengolahan Limbah Lilin Maha Vihara Duta Maitreya Monastery menjadi Lilin Fungsional Berbasis Ekonomi Sirkular: Pengolahan Limbah Lilin Maha Vihara Duta Maitreya Monastery menjadi Lilin Fungsional Berbasis Ekonomi Sirkular - Elvyra Danotti; Sri Wahyu Nensi (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2025)
Maha Vihara Duta Maitreya Monastery, Bukit Beruntung, Sungai Panas, Batam Kota is one of the places of worship for Buddhists that has a large number of visitors, especially during Vesak. The increase in visitor frequency also consistent with an increase in candle sales, especially lotus candles. Lotus candles be used as a symbol of illumination, purity, life, inner cleanliness, or a sacrifice. The use of large lotus candles results in an increase in the volume of wax waste. Used wax waste can have a negative impact on the environment if not processed properly. Because of the potential negative impacts caused by piles of wax waste, researchers are processing the available waste to be able to reuse wax waste. Through the processing of waste candles, recycled functional candles were obtained with various variations such as almond, brick, brick & brick pink and others that allow lighting within ± two hours. Thus, this research has contributed to efforts to increase public awareness through the action of reducing the volume of waste through reprocessing into recycled products that have a selling value in the community according to the principles of circular economy.